In-operando high-speed microscopy and thermometry of reaction propagation and sintering in a nanocomposite - Haiyang Wang (Nature Portfolio, 2019)
Imaging highly exothermic reactions in high spatial and temporal resolution to understand their underlying reaction mechanisms is challenging. Here, the authors develop a high-speed microscopy/pyrometry imaging system to successfully observe reactive sintering in a nanothermite reaction in-operando.